A vida nunca tá ruim, a vida sempre taboa: o artesanato do Vale do Jequitinhonha e a antropologiana perspectiva da extensão universitária - Daniela Guimaraes Vieira (2010)
This work deals with the craft production of Jequitinhonha Valley, especially the manufacturing group of pottery of the municipality on Caraí. From the standpoint of university extension, which here is configured as one of the interventions in local communities, describes the experiences of the Handicraft Cooperative project, conducted in 2009, relating the reflexes arising for this to studies on the region of Jequitinhonha Valley and crafts produced there. The life improved? The project was successful? From the ethnography, I show that any intervention must consider the "total social context", and that the tension about tradition and modernity continue to challenge researchers, even if it have a very different meaning to the groups.